Premenarche bilateral giant juvenile fibroadenoma of breast: literature review with a case report - Raleng, Mezhuneituo; Anand, Sameer; Kannur, Shailesh (International Surgery Journal, 2021)
Fibroadenoma is a common abnormality which every surgeon has been exposed to, and there are several international guidelines regarding its management. However giant fibroadenomas, especially in the premenarche setting has been a rare occurrence, even for the experienced surgeon. Various reports have shown that we need to treat this condition more aggressively than the normal fibroadenoma, and issues of cosmesis in a developing breast along with the aim to preserve lactation functionality becomes an issue. Since these cases remain a single life time experience for most surgeons, there is a sparsity of treatment protocols even in literature. Through this paper we hope to shed some valuable insight to this rare disorder and help surgeon colleagues, when dealing with similar cases.